Solve for t t+11=3t-7

Math
t+11=3t-7
Move all terms containing t to the left side of the equation.
Tap for more steps…
Subtract 3t from both sides of the equation.
t+11-3t=-7
Subtract 3t from t.
-2t+11=-7
-2t+11=-7
Move all terms not containing t to the right side of the equation.
Tap for more steps…
Subtract 11 from both sides of the equation.
-2t=-7-11
Subtract 11 from -7.
-2t=-18
-2t=-18
Divide each term by -2 and simplify.
Tap for more steps…
Divide each term in -2t=-18 by -2.
-2t-2=-18-2
Cancel the common factor of -2.
Tap for more steps…
Cancel the common factor.
-2t-2=-18-2
Divide t by 1.
t=-18-2
t=-18-2
Divide -18 by -2.
t=9
t=9
Solve for t t+11=3t-7

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top